2013
DOI: 10.1016/j.biomaterials.2013.01.069
|View full text |Cite
|
Sign up to set email alerts
|

In vivo performance of polymer nanocarriers dually-targeted to epitopes of the same or different receptors

Abstract: Modification of drug delivery nanomaterials with affinity molecules that facilitate targeting, has rendered a new class of ligands for cell receptors, which often possess valency and dimensions different from natural counterparts. Designing strategies to target multiple receptors or, never explored, multiple epitopes on the same receptor may modulate the biodistribution properties of these nanomaterials. We examined this using antibody-directed targeting of polymer nanocarriers to transferrin receptor (TfR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 52 publications
1
49
0
1
Order By: Relevance
“…ICAM is widely explored as an attractive endothelial target in the context of inflammation. Quantitatively, results of animal experiments involving ICAM targeting vary depending of specification of employed antibodies, carriers, animal models and conditions, but most, if not unanimously all studies showed accumulation of ICAM-targeted carriers in the pulmonary vasculature [26,44,[54][55][56].…”
Section: Discussionmentioning
confidence: 98%
“…ICAM is widely explored as an attractive endothelial target in the context of inflammation. Quantitatively, results of animal experiments involving ICAM targeting vary depending of specification of employed antibodies, carriers, animal models and conditions, but most, if not unanimously all studies showed accumulation of ICAM-targeted carriers in the pulmonary vasculature [26,44,[54][55][56].…”
Section: Discussionmentioning
confidence: 98%
“…administration in mouse models, as compared to free enzyme. 181,[183][184][185][186] For instance, ICAM-1-targeted nanocarriers achieved ~200-fold and ~15-fold enhanced enzyme accumulation in the lung and liver (major targets for type B NPC disease), ~5-fold and ~1.5-fold increases in the heart and kidneys (major targets for Fabry disease), and ~10-fold and ~6-fold increases in the heart and skeletal muscle (major targets for Pompe disease), respectively. 181,185,186 Additionally, ICAM-1-targeted nanocarriers tested in cell cultures improved uptake, lysosomal transport, and lysosomal degradation of the intended substrate compared to free enzymes.…”
Section: Challenges Of Ert For Lsds Nanocarrier Benefitsmentioning
confidence: 99%
“…179,180 This is possible due to specific ICAM-1-mediated activation of the sodium-proton exchanger protein NHE1 and the sphingomyelin/ceramide pathway, which regulate the physicochemical properties of the cell surface and reorganization of the cytoskeleton into actin stress fibers, facilitating engulfment and endocytosis of micron-sized objects targeted to ICAM-1. 46,179,180 Several studies used model polystyrene nanocarriers or biocompatible PLGA counterparts to improve delivery of recombinant lysosomal enzymes by targeting ICAM-1, including acid sphingomyelinase (ASM) deficient in types A and B Niemann-Pick disease, 179,[181][182][183][184] α-galactosidase A deficient in Fabry disease, 55,185 and α-glucosidase deficient in Pompe disease. 186 This strategy reduced the circulation time of lysosomal enzymes (preferable to avoid immunogenicity), while providing enhanced enzyme accumulation in most LSD target organs after i.v.…”
Section: Challenges Of Ert For Lsds Nanocarrier Benefitsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Various nanoparticulate carriers, such as polymer conjugates, [1,2,5] polymeric micelles, [6,9] nanoparticles, [3,4,8] and liposomes, [7] are utilized to selectively deliver various anticancer agents at the tumor in a passive targeting manner.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3,5,9] Various targeting moieties or ligands (such as folic acid and cyclic RGD peptides) against tumor-cell-specific receptors have been immobilized on the surface of nanoparticulate carriers to deliver them within cells via receptor-mediated endocytosis. [2,3,5,9] Recently, porphyrins (either natural or synthetic) were reported to show preferential uptake and retention by tumor tissues [10] via ligand-receptor-mediated endocytosis of low-density lipoproteins (LDL). [11][12][13][14][15][16][17] It well known that porphyrins also can generate cytotoxic species for therapy (e.g.…”
Section: Introductionmentioning
confidence: 99%